Обзор программ анализа и мониторинга сетевого трафика - Волотка, В. С. (ХНУРЕ, 2011)
The software, most popular in the class, for the analysis of the traffic (snif-fers) and program for monitoring the network traffic are considered. The brief review and comparative analysis of opportunities, advantages and lacks of the specified software is carried out. The recommendations are given at the choice of this or that software for the decision determined, including specific tasks of the users.